Revealing the unsung community masjids of Gombak to the Nation’s history - Mohd Nawawi, Norwina; Denan, Zuraini; Hamat, Sufian; Shaharil, Muhammad Ihsan; Asif, Nayeem; Aripin, Srazali (2021)
History, in the making of any nation, is usually deep-rooted to a civilisation for which the Malay Peninsula, currently part of Malaysia, has many to unveil. The location of the Malay peninsula at the crossroad between east and west, i.e. the Indian Ocean and the South China Sea, had witnessed many traders and fortune seekers among the inhabitants of surrounding islands or the Malay Archipelago- Nusantara as well as the Arabs, Indian and the Chinese of mainland China. The lure of gold, silver, and tin brought along many migrants’ to settle in the peninsula with their families and culture and religion. This paper seeks to highlight the Sumatra community found in the heart of Kuala Lumpur, the capital city of Malaysia, through their three (3) masjids along the Gombak River. A historical and descriptive method through comparative studies were adopted to identify their respective architectural influence and the community function. The study had unveiled the unwritten camaraderie among the migrant through the establishment of these masjids. Although unique in its development, the architecture that ties to Javanese and yet Sumatran has to prevail and maintain the very community that established them in line with the teachings of Islam as a place of unity, piety and prosperity.